Effect of Mindfulness-Based Stress Reduction with 40 Hz Music on Anxiety and Quality of Life in Prolanis Patients with Diabetes Mellitus - Muhammad Akbar Sobarna; Fery Agusman Motuho Mendrofa; Dwi Indah Iswanti (Journal Of Nursing Practice, 2026)
Background: Anxiety is a common psychological problem experienced by patients with Diabetes Mellitus and can negatively affect disease management and quality of life. Mindfulness-Based Stress Reduction (MBSR) combined with 40 Hz music frequency is that may help reduce anxiety and improve quality of life in patients with chronic diseases. Purpose: This study aimed to analyze the effectiveness of MBSR with 40 Hz music frequency on anxiety and quality of life among Prolanis patients with Diabetes Mellitus. Methods: Study design used a quasi-experimental pretest–posttest control group. The sample consisted of 60 respondents, divided into intervention and control groups. The intervention group received an 8-week MBSR program combined with 40 Hz music frequency, while the control group received standard Prolanis care. Anxiety levels using the DASS-21 questionnaire, and quality of life was assessed using WHOQOL-BREF. Data were analyzed using Wilcoxon and Mann–Whitney tests. Results: The anxiety levels significantly decreased in the intervention group (mean difference = −10.15; p < 0.001), while no significant change was observed in the control group (p > 0.05). In addition, quality of life significantly improved in the intervention group (median increase = +16; p < 0.001), whereas the control group showed only a slight and non-significant improvement (p > 0.05). Conclusion: Mindfulness-Based Stress Reduction combined with 40 Hz music frequency is effective in reducing anxiety and improving quality of life among Prolanis patients with Diabetes Mellitus. This intervention can be integrated into primary healthcare services as a complementary nursing intervention to support holistic diabetes management.